Shear and extensional properties of kefiran - Piermaria, Judith Araceli (2016)
Kefiran is a neutral polysaccharide constituted by glucose and galactose produced by Lactobacillus kefiranofaciens. It is included into kefir grains and has several health promoting properties. In the present work, shear and extensional properties of different kefiran aqueous dispersions (0.5, 1 and 2% wt.) were assessed and compared to other neutral gums commonly used in food, cosmetic and pharmaceutics industries (methylcellulose, locust bean gum and guar gum). Kefiran showed shear flow characteristics similar to that displayed by other representative neutral gums, although it always yielded lower viscosities at a given concentration. For each gum system it was possible to find a correlation between dynamic and steady shear properties by a master curve including both the apparent and complex viscosities. When studying extensional properties of selected gums at 2% wt. by means of a capillary break-up rheometer, kefiran solutions did not show important extensional properties, displaying a behaviour close the Newtonian.